D. D. Bitchuk - Medical University, Staff of KN (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The article is devoted to the 80th anniversary D. D. Bitchuk — leading light of modern Ukrainian orthopedics and traumatology, an outstanding scientist, talented teacher, рrofessor.